The role of claudin-6 in chromophobe renal cell carcinoma - Erlmeier, Franziska; Zschäbitz, Stefanie; Mikuteit, Marie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra (Histology and Histopathology, 2023)
BACKGROUND: The prognostic value of Claudin-6 (CLDN6) in non clear cell renal cell carcinoma (RCC) is still unclear. AIM: To evaluate the prognostic impact of CLDN6 expression in a large cohort of chromophobe RCC (chRCC). MATERIAL AND METHODS: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimens were analyzed for CLDN6 expression by immunohistochemistry. RESULTS: 81 chRCC patients were eligible for analysis, thereof 10 (12.3%) patients were positive for CLDN6. No significant associations were found for CLDN6 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in overall survival (OS) for patients with CLDN6⁻ compared to CLDN6⁺ tumors (87.0% versus 62.5%; p=0.174). CONCLUSION: In chRCC CLDN6 expression is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2023-04-14